Applicability of low methane forage systems into voluntary carbon markets standards - Ruden, Alejandro; Costa Junior, Ciniro; Dittmer, Kyle M; Matiz Rubio, Natalia; Yigezu, Atnafe Yigezu; Mulat, Daniel; Gonzalez Quintero, Ricardo; Arango, Jacobo (2025)
Methane emissions from enteric fermentation by ruminants represent a significant challenge to global greenhouse gas (GHG) mitigation efforts. Our work aims to compare leading methodologies and standards aimed at reducing enteric methane emissions in livestock production: VCS (VM0041), VCS (VM0042), AMS-III.BK from the American Carbon Registry, and the Gold Standard (GS). These methodologies, tailored for dairy and beef cattle production, provide systematic approaches for achieving and verifying emission reductions while enhancing co-benefits such as productivity and livelihoods. Each standard addresses specific livestock production contexts. VCS (VM0041) and GS target methane reductions through feed supplementation in beef cattle, while AMS-III.BK focuses on strategic feed interventions in smallholder dairy systems. VCS (VM0042) extends its scope to include carbon sequestration by improving agricultural land management (ALM) practices. Across these methodologies, interventions aim to enhance digestion efficiency and reduce methane production per unit of product, such as milk or meat. System boundaries vary, encompassing ingredient production, transport, and farm-level activities. For example, VCS (VM0041) assesses feed supplement impact from production to application, while AMS-III.BK focuses on the entire lifecycle of dairy animals in smallholder systems. Monitoring requirements emphasize both direct measurements and modeled estimations, including IPCC Tier 2 approaches, ensuring that reductions are accurately quantified. Monitoring frequency ranges from annual data collection to updates every five years, depending on the methodology. Standards employ tiered approaches to establish baseline emissions, incorporating direct measurements, IPCC-based models, or default factors. Additionality criteria ensure that interventions represent new practices beyond regulatory requirements or common farming practices. For instance, GS mandates projects to demonstrate significant methane reductions compared to traditional feeding systems and prove that feed supplements would not have been adopted without project support. Uncertainty is addressed through conservative estimates in emission reduction calculations, accounting for variability in diet efficacy, animal health, and management practices. Rigorous third-party verification is central to all standards, involving site visits, data audits, and stakeholder consultations to ensure compliance and accuracy in reported outcomes. Beyond methane reduction, these standards deliver multiple co-benefits. AMS-III.BK and GS improve smallholder livelihoods by increasing productivity and income while promoting animal health and food security. VCS (VM0042) enhances ecosystem resilience through improved soil health and sustainable land use. Additionally, interventions under VCS (VM0041) and GS contribute to higher productivity in beef systems, reducing the carbon footprint of meat production while boosting farmer profitability. These methodologies exemplify the integration of scientific rigor and practical applications in mitigating methane emissions. They provide robust frameworks for measuring, reporting, and verifying reductions, promoting sustainable livestock management. As global livestock production systems evolve, these standards are critical for driving climate-smart agricultural practices, fostering economic resilience, and achieving global climate goals. Nevertheless, improving the accuracy of emissions and intensity accounting is not intended to divert responsibility from the livestock sector in mitigating GHG emissions. Rather, these tools aim to provide robustness for evaluating the impact of livestock, contributing to a clearer understanding of the real impact of mitigation strategies.